2021
DOI: 10.1101/2021.04.02.21254714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic Utility of Antigen Detection Rapid Diagnostic Tests for Covid- 19: A Systematic Review and Meta-Analysis

Abstract: Background: Early detection of coronavirus disease (COVID-19) infection to improve disease management, becomes the greatest challenge. Despite high sensitivity of RT-PCR, not only it was reported that 20-67% of infected patients have false negative results. Rapid diagnostic tests (RDTs) are widely used as a point-of-care test for SARS-CoV-2 detection in both pharyngeal and blood specimens. To be less time-consuming, not seem so costly, and requiring no special training make it more favorable, but the low sensi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…However, we are also aware of the presence of several studies reporting the poor performance of rapid antigen tests, including the RAHT 27,28 . The difference in the performance and sensitivity of rapid antigen tests, including the RAHT, may be due to such factors as the type of samples, the type of assays, the time of sample collection, the accuracy of sampling, and the transport and storage 21,29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we are also aware of the presence of several studies reporting the poor performance of rapid antigen tests, including the RAHT 27,28 . The difference in the performance and sensitivity of rapid antigen tests, including the RAHT, may be due to such factors as the type of samples, the type of assays, the time of sample collection, the accuracy of sampling, and the transport and storage 21,29 …”
Section: Discussionmentioning
confidence: 99%
“…27,28 The difference in the performance and sensitivity of rapid antigen tests, including the RAHT, may be due to such factors as the type of samples, the type of assays, the time of sample collection, the accuracy of sampling, and the transport and storage. 21,29 Finally, the RAHT is increasingly used for screening COVID-19…”
Section: Analyzes Of the Correlation Between Ct Values And Dso Bymentioning
confidence: 99%
“…Some studies have suggested low sensitivity in screening asymptomatic patients 29,31,32 . Various authors have cited lower sensitivity in patients with low viral load (high Ct values on RT-PCR); hence RT-PCR testing should continue to be offered where clinical suspicion is high 24,30,33 . The users should follow manufacturers laid down testing procedures to avoid potentially misleading false-negative or false-positive results.…”
Section: Discussionmentioning
confidence: 99%